The Oral Discourse: Trends in Perfecting Foreign Language Speech Skills - Normatova Nurjamol Normatovna (International Journal on Integrated Education, 2023)
The various attitudes towards the exterior life have already become an independent study and today more people began to be interested in the nature of speech trying to upgrade oratory skills. This explains why perfecting the speaking comprehension in both native and foreign language is so demanded than any other language skills. As each device of the language is connected with each other, the speaking competence is also interrelated with other language skills of listening, reading and writing which are required to be developed together to meet the needs of language learning. The following work analyzes the development of the speaking skill of English as a foreign language of the students of non-linguistic departments of Higher Education. Choosing non-linguistic sphere is explained with the frequency of language learning barriers which face the very students of this area more than others.